Exercise 4: Cross-National Fertility Differentials - Hughes, Marion (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This guide was compiled with your students in mind. The Demography Teaching Resources Guide presents course syllabi for undergraduate and graduate courses in demography as well as resources for data used in demographic analysis and classroom exercises. Several of the syllabi and learning exercises offer suggestions for using online or other electronically available data as well as utilizing technological tools for self-guided and classroom learning. Among the undergraduate level syllabi are included some introductory syllabi and accompanying exercises as well as some more specialized syllabi focusing on race, economics, family, health issues and the environment. The graduate syllabi submissions include nine different syllabi focusing on theory, methodology, and some specific areas of demographic study. The learning exercise section has been organized to supplement all of the syllabi and includes over thirty different exercises covering the broad range of demographic topics.